Testimony, historical discourse and memory in the narrative of José León Sánchez - Vargas Vargas, José Ángel (2021)
This article offers a critical approach to Jose Leon Sanchez’s narrative work by addressing the author’s manner of rewriting Costa Rican and Latin American reality, fundamentally in terms of testimonial forms, historical discourse and the recovery of memory as constitutive elements of identitarian processes. This analysis also distinguishes three main stages in Jose Leon Sanchez’s writing process: a first stage that ranges from his early works to La Luna de Hierba Roja (1983); a second one framed within the exploration of the possibilities of the historical novel in Latin American context with works such as Tenochtitlan (1986) and Campanas para Llamar al Viento (1989) and, lastly, a third stage where biography as a genre explores the life of key characters in Costa Rican cultural life, as it takes place in the novel Al florecer, las rosas madrugaron (2014). To conclude, this article reflects upon the national academic community’s need to direct a greater attention to Jose Leon Sanchez’s narrative work, deemed as a relational system where the narrator permanently exerts an evaluative function over the diegesis and characters of his work with the purpose of reaching better forms of human convivence and education to reach true social transformation.